British Cardiovascular Intervention Society Training Culture Focus Group Position Statement: Bringing Trainees and Trainers Together - Thomas R Gilpin; Holly Morgan; Christian Fielder Camm; Alexandra Moss; James Cotton; Raghav T Bhatia; Dan McKenzie; Rasha Al-Lamee; Simon Ray; Nick Curzen (Interventional Cardiology: Reviews, Research, Resources)
Unprofessional behaviour within cardiology has been well documented and commonly occurs within the cardiac catheterisation laboratory, with higher rates in interventional subspecialities. While most trainees have positive experiences and encounters within the catheterisation laboratory, around one in five report experiencing bullying. This not only has a significant negative impact on the individuals directly involved, but also on the wider multidisciplinary team; importantly, it will have a deleterious effect on patient safety. The British Cardiovascular Intervention Society established the Training Culture Focus Group in 2022 to analyse and offer potential solutions to this pressing issue. We recommend that a cohesive approach between trainers and trainees is the most effective way to reduce unprofessional behaviour incidents, thus improving departmental workplace culture and a subsequent reduction in adverse patient safety events. ,1,2 ,3 ,4 ,5 ,5 ,6,7 ,8 ,9 10 and ,1,2 on behalf of the